The relationship between competency and attitude towards job performance of non-academic staff in Universiti Tun Hussein Onn Malaysia (UTHM) / Nurhidayah Mohd Samian and Nabilla Nazan Rahman - Mohd Samian, Nurhidayah; Rahman, Nabilla Nazan (Faculty of Business and Management, 2014)
This study is an attempt to identify the relationship between competency and attitude towards job performance in Universiti Tun Hussein Onn Malaysia (UTHM). As Malaysian may become developed nation on year 2020, each organization must address on many challenges. So, each of an organization must have valuable human capital which called as employees. When employees must be very competent and very good attitude towards organization, the increment of job performance will excellent. Competency is assumed as systematic approach to aligning individual performance to business strategy and goals. It does also can be individual’s ability to do job which is involve knowledge and skills. Attitude is reaction among employees while they are working. While, job performance as total expectation of employers toward their employees who are different character when working. Many researchers debated either competency or attitude give greater impact toward job performance in organization. A questionnaire was used as the main data collection method. This study is conducted at UTHM's. There are 331 respondents from different education background and grade. This are form of from 2400 number of non-academic staffs involve on this survey. Pearson Coefficient Correlation analysis was used to be find direction and strength of correlation between each dependent and independent variables. Our dependent variable are job performance; independent variables are competency and attitude. The result analysis for this study found that, there is significant on both independent variable towards dependent variables. Furthermore, for the result give greater impact on job performance is attitude among employees. Last but not least, in order to encourage the future research on this area of study, researcher state a few recommendations. It will be highlighted the ideas for more factors that involve to improve job performance among employees on the organization.